Soluble ST2 in coronary artery disease: Clinical biomarkers and treatment guidance - Zhang, Junyan; Chen, Zhongxiu; Ma, Min; He, Yong (Frontiers in Cardiovascular Medicine, 2022)
The IL-33/ST2L signaling pathway, involved in the pathophysiological processes of several diseases, mainly plays anti-inflammatory and anti-fibrotic effects. Soluble Suppression of tumorigenicity 2 (sST2), which served as a competitive inhibitory molecule of this pathway is a member of the interleukin (IL)-1 family, a decoy receptor for IL33, thought to play a role in cardiac remodeling and the inflammatory process. However, the association between sST2 and coronary artery disease (CAD), one of the most common causes of heart failure, is still being explored. We, therefore, reviewed the research on sST2 in the field of CAD, hoping to provide cardiologists with new perspectives.